Tomato fruit carotenoid biosynthesis is adjusted to actual ripening progression by a light‐dependent mechanism. (January 2016) - Llorente, Briardo; D'Andrea, Lucio; Ruiz‐Sola, M. Aguila; Botterweg, Esther; Pulido, Pablo; Andilla, Jordi; Loza‐Alvarez, Pablo; Rodriguez‐Concepcion, Manuel
Summary: Carotenoids are isoprenoid compounds that are essential for plants to protect the photosynthetic apparatus against excess light. They also function as health‐promoting natural pigments that provide colors to ripe fruit, promoting seed dispersal by animals. Work in Arabidopsis thaliana unveiled that transcription factors of the phytochrome‐interacting factor (PIF) family regulate carotenoid gene expression in response to environmental signals (i.e. light and temperature), including those created when sunlight reflects from or passes though nearby vegetation or canopy (referred to as shade). Here we show that PIFs use a virtually identical mechanism to modulate carotenoid biosynthesis during fruit ripening in tomato ( Solanum lycopersicum ). However, instead of integrating environmental information, PIF‐mediated signaling pathways appear to fulfill a completely new function in the fruit. As tomatoes ripen, they turn from green to red due to chlorophyll breakdown and carotenoid accumulation. When sunlight passes through the flesh of green fruit, a self‐shading effect within the tissue maintains high levels of PIFs that directly repress the master gene of the fruit carotenoid pathway, preventing undue production of carotenoids. This effect is attenuated as chlorophyll degrades, causing degradation of PIF proteins and boosting carotenoid biosynthesis as ripening progresses. Thus, shade signaling components may have been co‐opted in tomato fruit to provide information on the actual stage of ripening (based on the pigment profile of the fruit at each moment) and thus finely coordinate fruit color change. We show how this mechanism may be manipulated to obtain carotenoid‐enriched fruits. Significance Statement: Phytochrome interacting factors (PIFs) are key components in perceiving shade. Here we show that tomato fruit adapted PIFs to sense and monitor the progression of ripening and the production of carotenoids. We further show that this mechanism can be manipulated to increase the levels of health‐promoting carotenoids in tomatoes.